Analisis Preferensi Konsumen Terhadap Pemilihan Gerai Minuman Kopi Waralaba dan Non-Waralaba di Kota Banjarbaru - Eka Fakhrina; Nuri Dewi Yanti; Yusuf Azis (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The development of the coffee industry in Indonesia has driven the proliferation of both franchise and non-franchise coffee shops across various cities, including Banjarbaru. This study aims to analyze consumer characteristics and the factors influencing purchase decisions at franchise and non-franchise coffee shops in Banjarbaru City. Data were collected through accidental sampling involving 110 respondents, with 55 each at Janji Jiwa Jilid 344 (franchise) and Kala (non-franchise). Data were analyzed using descriptive analysis for respondent characteristics with varimax rotation using SPSS 23. Results show that franchise coffee shop consumers were predominantly male (61.82%) aged 22-28, while non-franchise consumers were predominantly female (61.82%), both with SMA/Bachelor education levels and monthly coffee expenditure of ≤ IDR 300,000. Three preference factors were identified for each shop type. For franchise: (1) physical attributes and store accessibility (42.38%), (2) product attributes and aesthetics (12.56%), and (3) service and value attributes (10.34%). For non-franchise: (1) price, service and accessibility attributes (35.85%), (2) product and sensory characteristics (27.32%), and (3) physical and store location attributes (11.88%). The differences in dominant factors between the two types reflect the distinct differentiation strategies that coffee entrepreneurs in Banjarbaru should optimize.